Participatory qualitative research methodologies in health - Higginbottom, Gina; Liamputtong, Pranee, 1955- (Los Angeles : SAGE, 2015)
This guide to the essentials of doing participatory methods in a broad range of health contexts covers all of the stages of the research process, from research design to dissemination.--
chapter 1. What is participatory research? Why do it? -- chapter 2. Addressing ethical issues in PR : the Primacy of Relationship -- chapter 3. Designing participatory research projects -- chapter 4. Data management, analysis and interpretation -- chapter 5. Drawing conclusions from your research -- chapter 6. Engaging older people in participatory research -- chapter 7. Involving children and youth in participatory research -- chapter 8. Conceptualizing inclusive research - a participatory research approach with people with intellectual disability : paradigm or method? -- chapter 9. Diverse ethno-cultural groups and the use of participatory research -- chapter 10. The relationship between engaged scholarship, knowledge translation and participatory research -- chapter 11. Community-university partnerships : a case study -- chapter 12. Information and communications technologies and the potentials for participatory research.
Includes bibliographical references and index.
Description based on MARC record for print version.
Keywords: elektronické knihy; electronic books; Medical care -- Research -- Methodology; Medical care -- Research -- Citizen participation; Qualitative research; Community-Based Participatory Research; Qualitative Research; Medical care -- Research -- Methodology; Qualitative research